Circulating CTRP5 in rheumatoid arthritis: an exploratory biomarker study - Marjan Taherian; Simin Almasi; Saber Mehdizadeh; Banafshe Fazeli; Mahsa Kalantari; Paria Bayati; Salar Pashangzadeh; Nazanin Mojtabavi (BMC Rheumatology, 2022)
Abstract Background Rheumatoid arthritis (RA) is an inflammatory disease that is characterized by the overproduction of cytokines. Among the newly discovered cytokines are the adipokines which are primarily produced by and released from the adipose tissue and some immune cells, as well as synovial cells. they are involved in various immune responses and inflammatory processes. However, there are controversial data regarding the pro-inflammatory or anti-inflammatory effects of adipokines in different conditions. C1q/TNF-related protein 5 (CTRP5) is a newly identified adipokine and adiponectin paralogous protein, which has been shown to be correlated with inflammatory diseases. Accordingly, the present study was designed to investigate the serum levels of CTRP5 in RA patients and evaluate any possible alterations in comparison to healthy individuals. Methods Serum CTRP-5 levels were measured in 46 patients and 22 healthy controls by ELISA. The demographic, laboratory, and clinical features of the patients were also evaluated in order to find any correlations. Results Serum levels of CTRP-5 were significantly (p < 0.0001) higher in patients with RA (14.88 ± 25.55) compared to healthy controls (4.262 ± 2.374). There was a significant correlation between serum CTRP-5 levels and triglyceride (TG) (r: − 0.3010, p: 0.0498), as well as erythrocyte sedimentation rate (ESR) (r: 0.3139, p: 0.0457), C-reactive protein (CRP) (r: 0.5140, p: 0.0008), and the number of white blood cells (WBC) (r: 0.3380, p: 0.0307), which are considered as the markers indicating the extent of inflammation. Moreover, CTRP-5 was found to be correlated with interstitial lung disease (ILD) (r: 0.3416, p: 0.0385), a comorbidity associated with RA disease. Conclusion This study demonstrated the increased level of circulating CTRP-5 in RA patients, which correlated with some inflammation-associated parameters and RA-associated comorbidities. Our observations suggest CTRP-5 as a putative inflammatory biomarker in RA, which may be useful besides the other disease-related markers.